2008
DOI: 10.1007/s11104-008-9657-6
|View full text |Cite
|
Sign up to set email alerts
|

N-transfer through aspen litter and feather moss layers after fertilization with ammonium nitrate and urea

Abstract: When fertilizer is broadcast in boreal forest stands, the applied nutrients must pass through a thick layer of either feather moss or leaf litter which covers the forest floor. In a growth chamber experiment we tested the transfer of N through living feather moss or aspen litter when fertilized with urea ((NH 2 ) 2 CO) or NH 4 NO 3 at a rate of 100 kg ha −1 and under different watering regimes. When these organic substrates were frequently watered to excess they allowed the highest transfer of nutrients throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…However, the total bryophyte effect (decreased N‐fixation plus sequestration of N into tissues) does not account for enough N capital to fully explain the high δ 15 N response threshold at which P. sylvestris and soil N availability and mineralization rates changed (Tables 1 and 2). Other important processes, such as sequestration of N into humic substances (Nadelhoffer et al , 1999), N volatilization (Startsev et al , 2008), N leaching (Akselsson & Westling, 2005), and N uptake by shrubs (Nilsson & Wardle, 2005; Nordin et al , 2006) may limit the availability of anthropogenic N r to trees when the bryophyte layer becomes N saturated.…”
Section: Discussionmentioning
confidence: 99%
“…However, the total bryophyte effect (decreased N‐fixation plus sequestration of N into tissues) does not account for enough N capital to fully explain the high δ 15 N response threshold at which P. sylvestris and soil N availability and mineralization rates changed (Tables 1 and 2). Other important processes, such as sequestration of N into humic substances (Nadelhoffer et al , 1999), N volatilization (Startsev et al , 2008), N leaching (Akselsson & Westling, 2005), and N uptake by shrubs (Nilsson & Wardle, 2005; Nordin et al , 2006) may limit the availability of anthropogenic N r to trees when the bryophyte layer becomes N saturated.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, air humidity may be higher in some EG stands than in DA stands (Nihlgård, 1969) providing favourable growing conditions for mosses (Frisvoll & Presto, 1997). Almost all absorbed water, and the majority of absorbed nutrients, are provided by direct precipitation or forest throughfall; only the very top of the soil is exploited (Anderson & Bourdeau, 1955;Binkley & Graham, 1981;Weber & Van Cleve, 1984;Startsev et al, 2008). A thick moss layer may not be observed in some EG forests, such as frequently thinned stands.…”
Section: (2) Understorey: An Example Of Cascade Effectsmentioning
confidence: 99%
“…Because mosses have no root (only short rhizoids), no or limited cuticle, and very high SLA, they rely mainly on atmospheric inputs for their water and nutrient supply. Almost all absorbed water, and the majority of absorbed nutrients, are provided by direct precipitation or forest throughfall; only the very top of the soil is exploited (Anderson & Bourdeau, 1955;Binkley & Graham, 1981;Weber & Van Cleve, 1984;Startsev et al, 2008). Moss may thus act as an intercepting layer for water and nutrients, reducing their movement and recycling.…”
Section: Synthesis (1) Spermatophytes and Forest Functioningmentioning
confidence: 99%
“…Assuming the fixed N 2 is transferred to the soil, questions about the amount, extent and rates of the transferred N emerge. Several studies have shown that mosses represent a short-term (<1 year) N-sink due to efficient capturing and retaining of N from the atmosphere (Startsev and Lieffers, 2006; Startsev et al, 2008; Friedrich et al, 2011). However, mosses can turn into a long-term (>1 year) N source after disturbances like drying-rewetting and fire events (Carleton and Read, 1991; Wilson and Coxson, 1999), upon which N is released from cyanobacterial-N-enriched moss tissue and made available for N-cycling in soils.…”
Section: Where Does the N Go? The Fate Of The Fixed N2mentioning
confidence: 99%